Common Birds of Chitwan National Park, Nepal - Jha, Parveen Kumar (Journal of Advanced Academic Research, 2017)
This research paper gives checklist of common birds of Chitwan National Park, which is a wild-life protected area in south-central Nepal. It covers tropical and sub-tropical vegetation. It is first protected area and includes 932 sq. km. Common birds observed are about 170 belonging to 48 Avian families during 2013-2014. Present investigator has very minutely observed birds in habitat conditions. Bird species were recognized by very high binocular. Birds were thoroughly studied from point of view of Taxonomy. Machans were also erected for observing birds.